“Father ain ´t no longer the family boss” . Genre, family and generational break from El Burgués (The Burgeois) liberal-conservative focus (1971-1973) - Vicente, Martín (Centro Interdisciplinario de Investigaciones en Género. IdIHCS (CONICET - UNLP). Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata, 2020)
The article analyzes how the Argentine liberal-conservative magazine El Burgués (The Burgeois) (1971-1973) presented the issues of gender, family and generational change. The publication presented itself seeking a centrality for the liberal identity in dialogue with guidelines of other right-wing expressions, using new journalism criteria and appealing to ironic humor. If the impossibility of establishing a post-Peronist political model in the Cold War world defined the political concerns of the fortnight, the changes of “the long sixties” were central to its approach on the axes of this article, wich resulted in a political reading of social and cultural phenomena.